Response of Vermicompost and Urea Combination Fertilizer Doses on the Growth and Yield of Scallion Plants (Allium fistulosum L.) - Fauziah, Fithriyatul; Setiyono, Setiyono; Usmadi, Usmadi; Purnamasari, Ika; Patricia SM, Susan Barbara; Arum, Ayu Puspita; Savitri, Dyah Ayu (International Journal on Food, Agriculture and Natural Resources, 2024)
Leeks (Allium fistulosum L.) are short-lived horticultural crops and have great commercial potential. The productivity of leeks in Indonesia, especially in the East Java region, is experiencing fluctuations, this is due to the problem of decreasing soil fertility. The use of inorganic fertilizers is one of the causes of decreasing soil fertility where the use of inorganic fertilizers in Indonesia reached 105.22 kg/ha, being the highest use compared to several countries in Southeast Asia. Therefore, I offer a solution to this problem, namely by combining the use of inorganic fertilizer with organic fertilizer, for this you can use urea fertilizer and vermicompost fertilizer, where vermicompost fertilizer has advantages compared to other compost fertilizers in terms of complete content starting from microorganisms, growth hormones, and nutrients. The aim of the research I conducted was to determine the interaction of applying urea fertilizer and vermicompost on the growth and yield of leek plants (Allium fistulosum L). The research was conducted at the Green House using a Completely Randomized Design (CRD) with 2 factors, each of which had 3 levels and was repeated 3 times to obtain 27 plant units. The first factor was a vermicompost dose of 0 g/polybag, 75 g/polybag, and 150 g/polybag, while the second factor was a urea dose of 0 g/polybag, 1 g/polybag, and 2 g/polybag. The experimental results showed that the best dose for the combined interaction of vermicompost and urea fertilizer treatment was 75 g/polybag vermicompost and 2 g/polybag urea to increase the number of leaves and height of leek plants.